Leaf anatomical characteristics in safflower genotypes as affected by drought stress - Bahrami, Forouzan; Arzani, Ahmad; Amini, Hajar (Acta Biologica Szegediensis, 2013)
Safflower (Carthamus tinctorius L.) is a drought-tolerant species that grows in arid and semi-arid environments exposing to long periods of water deficit stress. Structure and functions of the plant organs including leaf anatomy are affected by drought stress. The objective of this study was to evaluate the effects of drought stress on some leaf anatomical traits including leaf thickness, upper and lower epidermal thickness, xylem width, metaxylem diameter, and vascular bundle width and their relationship with grain yield using 20 safflower genotypes under field conditions. A randomized complete block design was used in each of the non-stress and drought stress field conditions. Analysis of variance showed that drought stress significantly reduced all variables measured except vascular bundle width. The results also revealed the positive and significant correlations between grain yield with leaf thickness (r = 0.53**) and xylem width (r = 0.51**) under drought stress conditions. Due to this fact, the leaves thickness and xylem width could be considered key structural features of leaves that manage the ability of a safflower genotype to tolerate water deficit stress. Therefore these traits could be used as criteria to select tolerant genotype that were more tolerant to drought.